Analysis of Segmentation and Targeting User Inpatient Services Are Not JKN Participants in Muhammadiyah Hospital Ponorogo - Iis Kartika (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2017)
Muhammadiyah Ponorogo Hospital as Advanced Health Facility still suffers a lot of problem in providing patient service of JKN participant, meaning that the health insurance benefit has not been optimally felt by hospital as supporting of JKN program. Opportunities of service management of JKN participants, especially the users of inpatient services are not expected to have the leverage in optimizing the hospital's financial performance, it is necessary to conduct research on the users of inpatient services instead of JKN participants with the aim of getting a deeper picture and understanding of segmentation and targeting of inpatient service users are not JKN participants. The type of this research is descriptive research with quantitative approach and discussion of targeting is analyzed based on interpreter interpretation. The user segmentation of inpatient services is not a JKN participant with the Two Step Cluster SPSS Version 20 analysis, forming seven clusters but with poor model quality. Of the seven clusters that are targeting are clusters 1,7 and 6, with their respective meanings. The average demographic segmentation is 20-50 years old, elementary-high school education, members of the Family Card of 3-6 people, and includes the lower middle-income socio-economic group, in Sukorejo, Sawoo and Sampung sub-districts. Knowledge of JKN services of all clusters is lacking, but with positive perceptions of JKN and an attitude of interest to become a participant of JKN insurance